Implementasi Media Interaktif Budidaya Kelapa Sawit Bagi Komuditas Tani Berbasis Android - Ulul Azmi Harahap; Sumi Khairani; Dharmawati (Universitas Harapan Medan, 2021)
Palm oil is an industrial plant / plantation used as a producer of vegetable oils, industrial oils and fuels. There are two types of oil palm, elaeis guineensis and elaei soleifera, which are used to produce palm oil in commercial agriculture. In fact, many communities (farmers) have failed or are still minimal in oil palm management. These factors include land conditions, knowledge of farming and insufficient experience. One way to provide knowledge to oil palm farmers is through socialization. Socialization which is equipped with media in accordance with technological developments will facilitate and greatly help the community. It will be easier for the community to obtain information about oil palm cultivation. The purpose of this study is to provide an attraction for oil palm cultivation. Then this research uses Unity 3D software by utilizing augmented reality technology. The results of this study are an android-based application about oil palm cultivation that has augmented reality technology. In the interactive media introduction of palm oil using Augmented reality technology, there are questionnaire results that conclude the first question questionnaire gets 62.6% results, the second question gets 64%, the third question gets 64%, the fourth question gets 64% and the last question 78.6%.